Followers of Harvard Study - Kenichi KUWASHIMA (Annals of Business Administrative Science, 2013)
A diversification of research approaches became apparent in the field of product development management in the 1990s, ased on a monumental study by Clark and Fujimoto (1991) (the so-called “Harvard Study”). The following five new research approaches then came into play. The “product-industry based approach,” sought to clarify effective product development management by focusing on the characteristics of products and industry. The “multi-project approach” analyzed multiple projects over single projects. The “dynamic approach" focused on the dynamic aspects of product development from the long-term perspective. The “problem-solving approach” regarded product development as a problem-solving process. The “organizational capability approach” sought to elucidate organizational capabilities that contribute to high performance in product development.